Artificial intelligence in decision-making - Wan Ishak, Wan Hussain; Mat Yamin, Fadhilah (2001)
Decision-making is a complex process that involves data that is derived based on set of rules. Conventional computer programs that executes the rules structurally, limits the decision-making process.In addition, the computer (or machine) itself does not have power to think and formulate the rules by itself (based on experience). This paper presents the potential use of Artificial Intelligence (AI) techniques in management, specifically in decision-making. A1 is a science that tries to emulate human "technology" onto a computer or machine. A1 contributes to a highly complex decision making procedure exhibits from a set of predefined rules. Some of AI techniques can learn patterns, mapping, optimizing and interprets fuzziness. Several of these techniques are discussed based on its function (potentials) and contribution to decision-making process.